1999
DOI: 10.1016/s0960-9822(99)80058-x
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular signalling: PDK1 – a kinase at the hub of things

Abstract: Phosphoinositide-dependent kinase 1 (PDK1) is at the hub of many signalling pathways, activating PKB and PKC isoenzymes, as well as p70 S6 kinase and perhaps PKA. PDK1 action is determined by colocalization with substrate and by target site availability, features that may enable it to operate in both resting and stimulated cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
175
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(179 citation statements)
references
References 21 publications
3
175
1
Order By: Relevance
“…Protein kinase B (PKB, also called c-Akt) is thought to play a role in mediating some of the metabolic actions of insulin, as well as the effects of survival factors on apoptotic processes [1][2][3]. PKB is only active when phosphorylated at two residues, Thr-308 and Ser-473 [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein kinase B (PKB, also called c-Akt) is thought to play a role in mediating some of the metabolic actions of insulin, as well as the effects of survival factors on apoptotic processes [1][2][3]. PKB is only active when phosphorylated at two residues, Thr-308 and Ser-473 [1].…”
Section: Introductionmentioning
confidence: 99%
“…The phosphorylation of Thr-308 only occurs in itro and in i o in the presence of PtdIns(3,4,5)P $ or PtdIns(3,4)P # and, for this reason, the protein kinase found to phosphorylate this residue has been termed 3-phosphoinositidedependent protein kinase-1 (PDK1) [4]. Thr-308 is located in the activation loop of the catalytic domain of PKBα, in a region that displays high homology between different AGC family members (cAMP-dependent, cGMP-dependent and PKC) [1][2][3]. Other members of the AGC subfamily of protein kinases, including p70 ribosomal S6 protein kinase (p70 S6K) [5], protein kinase C (PKC) isoforms [6], serum-and glucocorticoid-induced protein kinase (SGK) [7] and the cAMP-dependent protein kinase (PKA) [8], also possess residues lying in a sequence motif equivalent to Thr-308 (termed the PDK1 phosphorylation site) whose phosphorylation is required for activation.…”
Section: Introductionmentioning
confidence: 99%
“…Pdk1p is closely related to phosphoinositide dependent protein kinases identified in different eukaryotic organisms (Figure 1). PDK1 is one of the two key effectors of the insulin/insulin-like growth factor-1 signaling pathway (reviewed in Belham et al, 1999;Pearl and Barford, 2002;Mora et al, 2004). Studies in mammalian cells have shown that PDK1 phosphorylates and activates the AGC kinase members regulated by phosphoinositide 3-kinase (reviewed in Belham et al, 1999;Peterson and Schreiber, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…PDK1 is one of the two key effectors of the insulin/insulin-like growth factor-1 signaling pathway (reviewed in Belham et al, 1999;Pearl and Barford, 2002;Mora et al, 2004). Studies in mammalian cells have shown that PDK1 phosphorylates and activates the AGC kinase members regulated by phosphoinositide 3-kinase (reviewed in Belham et al, 1999;Peterson and Schreiber, 1999). In Drosophila, dPDK1 functions as a central regulator of cellular and organism growth by controlling AGC kinases Akt and S6K (Rintelen et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Like Akt and PDK1, which play key regulatory roles in the upstream of the TOR pathway (Burgering and Coffer, 1995;Pullen et al, 1998), S6K1 also belongs to the AGC kinase family of serine/threonine kinase. Phosphorylation of S6K1 at its carboxy-terminal regulatory domain by TOR appears to be a prerequisite for its full activation, which requires the PDK1-dependent phosphorylation at the activation loop of the catalytic domain (Belham et al, 1999). In addition to its well-known target, ribosomal protein S6 (Chung et al, 1992;Price et al, 1992), several other substrates of S6K1 have been also identified recently in mammalian cells, the roles of which are all implicated in the protein synthesis as well (Ma and Blenis, 2009).…”
Section: Introductionmentioning
confidence: 99%